Optimizing Sowing Window for Local and Chinese Elite Lines under Changing Climate - Bismillah Khan; Muhammad Arif; Fazal Munsif; Muhammad Mehran Anjum; Elżbieta Wójcik-Gront; Aziz Khan; Ijaz Ahmad; Yong Ren; Changping Zhao; Xiangzheng Liao; Shengquan Zhang (Agronomy, 2022)
Climate change threatens major global crops including wheat of subtropical regions, especially during critical developmental stages. To address this concern, researchers try to identify exotic genetic diversity with pronounced stress tolerance or avoidance or find improved genotypes with optimal sowing time. Current research evaluated seven exotic Chinese wheat genotypes (MY4094, MY1617, MY1416, MY2914, MY1501, MY1419, and MY902) for yield and associated characters along with a local check variety (PS-15) under optimal (1st November), moderate (16th November), and late sowing times (1st December) during both years. The result revealed that delayed sowing reduced yield and yield components of the tested genotypes, including the local check. Genotype MY1617 performed best under optimal sowing in terms of grain yield and yield attributes, with a 5% increase over the local check. MY902 had the highest seed yield among late-sown genotypes. Correlation analysis showed that grain yield was positively correlated with grains per spike, days to anthesis, booting, and heading. The current study provides important information for wheat breeders to exploit exotic genetic materials under a diverse sowing window and develop genotypes with improved traits that may boost wheat growers’ production.